Pemanfaatan Teknologi Tepat Guna Untuk UMKM Barokah 717 di Desa Ambulu Kecamatan Sumberasih Kabupaten Probolinggo - Yoseph Santovino Roso; Sonja Andarini (Jurnal Insan Pengabdian Indonesia, 2023)
On this activity, the author’s focus is on helping Barokah 717 MSMs located in Ambulu Village, Sumberasih District, Probolinggo Regency to manufacture Appropriate Technology the cover of cassava and banana slices to improve the function of existing equipment. The hope is that through upgrade of this tool can increase work productivity. Another purpose of this activity is also as a forum for author to improve entrepreneurial skills through the manufacture of equipment. The method used is observation, discussion, and experimentation. With this activity, hoped that the tool that created may help Barokah 717 work productivity. The cover for the cassava and banana slicing that the author made includes a block that is used to press cassava or bananas so that no longer use hand directly. The problem faced is that because the tool is still experimental, when it tested it is not optimal operated and also the difference isn’t significant, then the availability of equipment to make that tool is limited.